Tribesourcing Southwest Films: Counter-Narrations and Reclamation - Dollman, Melissa; Sorrell, Rhiannon; Jenkins, Jennifer L. (KULA, 2021)
As a work in progress, the Tribesourcing Southwest Film Project seeks to decolonize midcentury US educational films about the Native peoples of the Southwestern United States by recording counter-narrations from cultural insiders. These films originate from the American Indian Film Gallery, a collection awarded to the University of Arizona (UA) in 2011. Made in the mid-twentieth century for the US K–12 educational and television markets, these 16 mm Kodachrome films reflect mainstream cultural attitudes of the day. The fully saturated-color visual narratives are for the most part quite remarkable, although the male "voice of God" narration often pronounces meaning that is inaccurate or disrespectful. At this historical distance, many of these films have come to be understood by both Native community insiders and outside scholars as documentation of cultural practices and lifeways—and, indeed, languages—that are receding as practitioners and speakers pass on. The Tribesourcingfilm.com project seeks to rebalance the historical record through collaborative digital intervention, intentionally shifting emphasis from external perceptions of Native peoples to the voices, knowledges, and languages of the peoples represented in the films by participatory recording of new narrations for the films. Native narrators record new narrations for the films, actively decolonizing this collection and performing information redress through the merger of vintage visuals and new audio.